Granulosis rubra nasi: A rare dermatosis not limited to nose - Mahesh Mathur; Neha Thakur; Sunil Jaiswal; Srijana Maharjan; Anjali Shrestha; Supriya Paudel (Wiley, 2024)
Abstract Granulosis rubra nasi (GRN) is a rare genodermatosis involving the eccrine glands with an unknown aetiology. It is clinically characterized by localized hyperhidrosis, erythema, papules, pustules, and vesicles over central region of face and usually manifests during early childhood. GRN is asymptomatic, spontaneously resolves during puberty, and treatment options have inconsistent results. We hereby present a case of GRN in 38 years female with sites and dermoscopy findings not defined so far.